How is the high vaginal swab used to investigate vaginal discharge in primary care and how do GPs' expectations of the test match the tests performed by their microbiology services?. Issue 3 (28th May 2004) - Noble, H; Estcourt, C; Ison, C; Goold, P; Tite, L; Carter, Y H
Abstract : Objectives: To describe the management of vaginal discharge in general practice, with particular regard to the use of the high vaginal swab (HVS), and to compare GPs' expectations of this test with the processing and reporting undertaken by different laboratories. Methods: A postal questionnaire survey of 2146 GPs in the North Thames area and postal questionnaire study of the 22 laboratories serving the same GPs were carried out. GPs were asked how they would manage a young woman with vaginal discharge and what information they would like on an HVS report. Laboratories were asked how they would process and report on the HVS sample from the same patient. Results: Response rate was 26%. 72% of GPs would take an HVS and 62% would refer on to a genitourinary medicine (GUM) clinic. 45% would offer empirical therapy and 47% of these would treat for candida initially. 75% of GPs routinely request "M, C&S" on HVS samples but 55% only want to be informed about specific pathogens. Routine processing of HVS samples varies widely between laboratories and 86% only report specific pathogens. 78% of GPs would like to be offered a suggested diagnosis on HVS reports, and 74% would like a suggested treatment. 43% of laboratories ever provide a diagnosis, and 14% provide a suggested treatment. Conclusions: GPs frequently manage vaginal discharge and most of them utilise the HVS. GPs' expectations of the test are not well matched to laboratory processing or reporting of the samples.